Advances in Food Safety and Environmental Engineering: Proceedings of the 4th International Conference on Food Safety and Environmental Engineering (FSEE 2022), Xiamen, China, 25-27 February 2022 - Haddout, Soufiane (CRC Press, 2022)
Advances in Food Safety and Environmental Engineering is a compilation of selected papers from the 2022 4th International Conference on Food Safety and Environmental Engineering (FSEE 2022) and focuses on the research of food engineering and environmental engineering. The proceedings feature the most cutting-edge research directions and achievements related to health and environment. Subjects in these proceedings include: Food Safety and Health Food Nutrition Food Processing and Preservation Environmental Engineering and Technology Ecology and Ecosystem Management This collection of papers aims to promote food safety and environmental development, resource sharing, flexibility and high efficiency. An additional goal is to promote scientific information exchange globally between scientists from the best universities, research centers and high-tech companies. Electrochemical treatment of refractory organic compounds in a double-cathode system; Luyuan Miao, Ye Jiang, Wucheng Han, Xingchi Chen, Yue Quan Effects of food education on nutrition knowledge and related behaviors of elementary school students in Xin County, China; Yangzhou Zhang, Jiguo He Effects of pyroligneous acid amendment on avoidance, survival and biomass change of earthworms in an agricultural soil; S.Y. Cheng, Q. Liu Development of health characteristic mashed potato; Songyun Yu, Tong Zhang Study on the stability of corn stigmas oral liquid; Yunwen Zhu, HaiPing Tian, Bing Li, Hongli Zhou Effects of different biological enzymes on preparation of tea seed oil diglyceride; Jingzhi Wu, Jingjing Xiao, Aihua Zhang, Zhihong Xiao, Hongmei Wu Environmental model of meteorological risk of strawberry powdery mildew in solar greenhouse; Zhangyan Le, Yanyan Zhang, Qucheng Wei, Minghua Shi, Peng Zhou Status of Camellia processing and utilization; Jia Tu, Ruicong Tang, Desheng Kang, Zhihong Xiao, Aihua Zhang Correlation between caffeine consumption and emotion regulation; Xinying Wang Effects of freeze-thaw pretreatment on the physicochemical properties of microwave-dried beetroots; Yan Liu, Zhenhua Duan, Sergei Sabadash, Xiaoxian Tang Analysis of fruit and vegetables plan in China based on national nutrient intake model; Zhuo Hao Different essential oil on antifungal activity of grape Fusarium sp.; Y.D. Xie, J.W. Zhu, H.Y. Liu, H.S. Lian, J. Liu Aromatic compounds of pineapple (Ananas comosus cv. MD-2) in different harvest time; Shenghui Liu, Zhuying Zhu, Yumei Zhang, Wenqiu Lin, Changbin Wei, Xiumei Zhang Electrochemical sensor for sensitive determination of nitrite based on the Fe-N-C materials; Xiaonan Liu, Tingting Zhang, Shiyun Ai A study on preparation of gastrointestinal digestive release of different contents of hemoglobin by enzymatic hydrolysis; Zurong Song, Ali Tao, Xuehua Feng Study on improving the performance of mortar based on phosphogypsum with phosphorus slag powder; Bin Sun, Shaocong Zheng Environmental technology and ecological environment governance Engineering practice study on the treatment of domestic garbage leachate based on two-stage disc tube reverse osmosis combined process; Xingfu Xue Time-resolved fluorescence immunoassay for detection of CEA in saliva; Shuangshuang Zhao, Shengnan Zhao, Yan Guo Electrochemical oxidation of organic pollutant using a double cathode system; Wucheng Han, Luyuan Miao, Tingchun Yan, Yansong Liu, Yue Quan City size, population concentration and environmental pollution: Evidence from China; Jinkai Li Preliminary study on the design simulation scheme of sponge campus based on LID; Shihao Shen, Jie Wu, Jinmei You, Zhangbo He, Xun Wang, Xian Liu, Qingping Jin Study on the Evaluation Method for Safety Operation of Medium and Small Earth-Rock Dam in Cold Regions; Yawei Li, Zhigang Yin, Peijiang Cong, Liang Wang Analysis on industrial water consumption and countermeasures on water saving in Yangtze River Basin; Zhiguo Gan, Chao Wang, Wenjuan Chang Research and application of bioretention to treatment runoff rainwater; Leixiang Wu, Ang Li, Xingchen Liu, Zhuowei Wang, Ronghao Guan Study on ecological treatment of tail water by different wetlands; Dingguo Jiang, Yiqing Gong, Hanmei Li, Jie Dai Research on the development and utilization model of unconventional water resources in China; J.T. Zheng, X.X. Deng Research and exploration of soil and water conservation ratio in red soil region of southern China; Dongbing Cheng, Yuanling Zhao, Shengyu Shen, Songhua Xie, Shengsheng Xiao, Guimiao Dou, Zikang Chen, Jicheng Ma Refined assessment of marine disaster risks in coastal areas; Hongkuan Liu Study on the evaluation system of ecological waterways; Yan Wang, Runzuo Guo Study on the anti-fracture features of straight roots of desert control plants; Xin Zhang, Jing Liu, Jianying Guo, Tiejun Liu, Tiegang Zhang, Zhengqi Yang, Ruishen Li Spatial autocorrelation analysis of land-use changes and ecosystem services value in Changsha City; Shengfeng Liu Characterization of changes in extreme precipitation events in Yuanzhou District, Guyuan City, 1957–2016; Deng Zhang, Chaochao Li, Chenglu Li, Haoli Xu Existence of a huge isothermal water mass in the bottom water body of Jiaozhou Bay; Dongfang Yang, Danfeng Yang, Huijing Xing, Sivakumar Manickam, Haixia Li Mechanism for the variation of water temperature in Jiaozhou Bay; Dongfang Yang, Xiaoju Zhang, Danfeng Yang, Sivakumar Manickam S. Haddout is a researcher in fluid mechanics and modeling in the Department of Physics, Faculty of Science, Ibn Tofail University, Morocco. To date, he is the author of 1 book, 2 submitted books, and published more than 45 refereed journal articles with 35 refereed articles as the first authors listed; and expert reviewer with AEIC-Academic Exchange Information Centre (China). Dr. Haddout is a reviewer for many project proposals from international universities; he received more than 80 certificates from international conferences and renowned journals; he has bee an invited speaker for many international conferences and co-convener for special scientific sessions to the Coastal and Estuarine Research Federation 2021 (United States).